1997
DOI: 10.1172/jci119681
|View full text |Cite
|
Sign up to set email alerts
|

The effects of total lymphocyte deficiency on the extent of atherosclerosis in apolipoprotein E-/- mice.

Abstract: Activated T lymphocytes are present in human atherosclerotic lesions and autoantibodies to antigens within lesions have been detected in serum, but the roles of the cellular and humoral immune systems in atherogenesis have not been determined. The effect of total lymphocyte deficiency on atherogenesis was investigated by crossing apo E-deficient mice (which develop atherosclerosis resembling human disease) with mice deficient in RAG2 (which is required for normal B and T lymphocyte development). Mice were plac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
146
3
3

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 233 publications
(161 citation statements)
references
References 46 publications
9
146
3
3
Order By: Relevance
“…However, the present finding of an association between autoantibodies against apo B peptides and CV death are well in line with accumulating evidence suggesting that immune responses against plaque antigens play an important role in atherosclerosis and that LDL is a major target for these immune responses. 16,17,21,22 Although initial studies argued for a proatherogenic effect of adaptive immunity in atherosclerosis 23 it has now become evident that the role of the immune system in the disease process is much more complex and that both pathogenic and protective responses are involved. Suppressive regulatory T cells protect against atherosclerosis through release of anti-inflammatory cytokines and suppression of autoreactive T cells in the artery wall.…”
Section: Discussionmentioning
confidence: 99%
“…However, the present finding of an association between autoantibodies against apo B peptides and CV death are well in line with accumulating evidence suggesting that immune responses against plaque antigens play an important role in atherosclerosis and that LDL is a major target for these immune responses. 16,17,21,22 Although initial studies argued for a proatherogenic effect of adaptive immunity in atherosclerosis 23 it has now become evident that the role of the immune system in the disease process is much more complex and that both pathogenic and protective responses are involved. Suppressive regulatory T cells protect against atherosclerosis through release of anti-inflammatory cytokines and suppression of autoreactive T cells in the artery wall.…”
Section: Discussionmentioning
confidence: 99%
“…2 Serum autoantibodies titers to modified lipoproteins were determined as described previously, with data expressed as the ratio of chromagen development for LDL compared with malondialdehydemodified LDL coated plates. 23 …”
Section: Measurement Of Serum Componentsmentioning
confidence: 99%
“…23,24 The maximum width of the abdominal aorta was measured using computerized morphometry (Image-Pro). Aneurysm incidence was quantified based on a definition of an external width of the suprarenal aorta that was increased by 50% or greater compared with aortas from saline-infused mice.…”
Section: Quantification Of Atherosclerosis and Aaamentioning
confidence: 99%
“…Two of these studies used lymphocyte-deficient RAG-null mice. In one study, cholesterol-fed RAG2/apoE double knockout mice were found to develop lesions at the same rate as "normal" apoE-null mice (30). Similarly, another group found that RAG1/apoE double knockout mice developed atherosclerotic lesions at essentially the same rate as normal apoE-null mice on a high-cholesterol diet (31).…”
Section: Introductionmentioning
confidence: 95%